Food carbohydrates - Cui, Steve W. (Taylor & Francis Group, LLC, 2011)
Unique in its broad range of coverage, Food Carbohydrates: Chemistry, Physical Properties and Applications is a comprehensive, single-source reference on the science of food carbohydrates. This text goes beyond explaining the basics of food carbohydrates by emphasizing principles and techniques and their practical application in quality control, product development, and research.